2020
DOI: 10.1080/02615479.2020.1715934
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the gendered academy: women in social work academia

Abstract: Women fare less well than men across all academic disciplines: they are less likely to be promoted, they earn less, and many more professors are men. There has, however, been little analysis to date of the experience of women in social work education, a discipline that has historically had higher representation of female staff and students. This study set out to explore women in the social work academy through a case-study of social work education in Scotland. A mixed methods approach was used, including a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…This is consistent with previous research that describes women's work in the private sphere as invisible and the inequities and structural barriers embedded within academic medicine and the pediatric clinicianscientist field as pervasive. 9,13,14,40,41 Caring responsibilities remain highly gendered, regardless of the number of caregivers in the home, 12 and women are expected to maintain the responsibility for household chores and to be the primary caregiver. 42 Consistent with our findings, graduate students, trainees, academics and clinicians of ethnic minorities face racism, discrimination and ongoing racial microaggressions within academic departments at every stage of the path during their training and practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous research that describes women's work in the private sphere as invisible and the inequities and structural barriers embedded within academic medicine and the pediatric clinicianscientist field as pervasive. 9,13,14,40,41 Caring responsibilities remain highly gendered, regardless of the number of caregivers in the home, 12 and women are expected to maintain the responsibility for household chores and to be the primary caregiver. 42 Consistent with our findings, graduate students, trainees, academics and clinicians of ethnic minorities face racism, discrimination and ongoing racial microaggressions within academic departments at every stage of the path during their training and practice.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Research demonstrates substantial challenges extending beyond the early career phase, including that women of colour are the least likely to secure research funding; 8,9 that biases affect publishing and the grant evaluation processes; 10 that women and racialized individuals entering the faculty rank are poorly compensated compared with males; 11 and that mentorship and role models may be harder for women to secure than their male counterparts. [12][13][14] Our recent scoping review found that research exploring the training and career paths of pediatric clinician-scientists from equity-seeking groups does not currently exist. 15 The individual-and system-level factors that will enhance equity, diversity and inclusion (EDI) among pediatric clinicianscientists are urgently needed to inform the evaluation frameworks and curricular content for pediatric clinicianscientist training programs.…”
mentioning
confidence: 99%
“…In this sense, social work is seen as a “dirty job for women,” because it serves stigmatized populations (Kreiner et al, 2006) and has a minor value in the social sciences (Aquín, 2003). So, we must constantly defend our value as women and social workers (Cree et al, 2020).…”
Section: Male Privilege In Social Servicesmentioning
confidence: 99%
“…Acker, 1990, p. 146). While this conceptualisation has been utilised by various studies across contexts (Conesa Carpintero & González Ramos, 2018;Cree, Morrison, Mitchell, & Gulland, 2020;Kantola, 2008), my study is the among the first which employed gendered organisations to demonstrate how the gendering practices in work setting feed into women's experience of inequalities in Vietnamese academic settings. To this end, my study also contributes to knowledge about the nature of Vietnamese academia, which has seldom been subjected to gender analysis.…”
Section: Vietnamese Heis As Gendered Organisationsmentioning
confidence: 99%